CONVERGENCE THEOREMS FOR LIPSCHITZ PSEUDOCONTRACTIVE NON-SELF MAPPINGS IN BANACH SPACES - Tufa, A. R.; Zegeye, H. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2016)
In this paper, we introduce an iterative process and prove strong convergence result for finding the fixed point of Lipschitz pseudocontractive non-self mapping in Banach spaces more general than Hilbert spaces. In addition, strong and weak convergence of Mann type sequence to a fixed point of λ-strictly pseudocontractive non-self mapping is investigated. Moreover, a numerical example which shows the conclusion of our result is presented. Our results improve and generalize many known results in the current literature.